(untitled) (المجلة الدولية للبحوث العلمية, 2026)
Introduction: Obstructive sleep apnea-hypopnea syndrome (OSA) is characterized by repeated episodes of upper airway obstruction, resulting in intermittent hypoxia and sleep fragmentation. These disturbances are likely to alter cognitive processes, in particular the various components of working memory. Objective: To study the relationship between the severity of OSA, defined by the type of apnea (apnea-hypopnea index, AHI), and the performance of the various components of the working memory according to the Baddeley model: phonological loop, visual-spatial notebook and central administrator. Methods: Cross-sectional correlational study conducted at the Hassan II University Hospital in Fez. The population includes adult patients followed by a somnology consultation, diagnosed by polysomnography. The memory assessment is based on the phonological loop (direct empan, WAIS-III), the visual-spatial notebook (Corsi blocks, MEM-III) and the central administrator (verbal and spatial empan, WAIS-III/MEM-III). The statistical analyses were carried out with the SPSS software. Results: The correlations reveal a strong link between the type of apnea and the phonological loop (r = 0.031; p = 0.8), a weak link with the visual-spatial notebook (r = 0.1; p = 0.1), and a strong and negative link with the central administrator, tested both via the verbal empanel (r = 0.03; p = 0.9) than spatial (r = -0.02; p = 0.8). This last negative correlation indicates that as the severity of apnea increases, the performance of the central administrator decreases. Conclusion: The SAHOS affects differentially the components of the working memory, with a selective and marked vulnerability of the central administrator. These results confirm the hypothesis of a preferential fragility of the executive processes and underline the need for a systematic neuropsychological evaluation in the management of apneic patients.